Here you can ask questions and find or give answers to organizational, academic and other questions about studying computer science.

1.1k questions

1.2k answers

1.6k comments

524 users

0 votes
Thank you for clear explanation. 
Can you please explain us this step. I understood till previous step.
¬φ =
        ¬a ∧   b ∧   c ∧  d ∨
         a ∧ (¬b ∧   c ∧  d ∨
               b ∧ (c ∨ d))
related to an answer for: Decision tree
in * TF "Intelligent Systems" by (850 points)

1 Answer

0 votes

Well, ¬d ∨ d is true, and second, we have theabsorption law ¬c ∧ d ∨ c = d ∨ c, so that we get

    ¬φ =
        ¬a ∧   b ∧   c ∧  d ∨
         a ∧ (¬b ∧   c ∧  d ∨
               b ∧ (¬c ∧  d ∨
                     c ∧ (¬d ∨ d )))
       =
        ¬a ∧   b ∧   c ∧  d ∨
         a ∧ (¬b ∧   c ∧  d ∨
               b ∧ (¬c ∧  d ∨
                     c ))
       =
        ¬a ∧   b ∧   c ∧  d ∨
         a ∧ (¬b ∧   c ∧  d ∨
               b ∧ (c ∨ d))

However, the simplifications were not really required, and they also do not matter for the construction of the BDD in the next part of the exam problem (since BDDs are the same for all equivalent formulas).

by (165k points) 1 flag

Related questions

Imprint | Privacy Policy
...